Implication of Land-Use and Land-Cover Change into Carbon Dioxide Emissions in Karang Gading and Langkat Timur Wildlife Reserve, North Sumatra, Indonesia - Mohammad Basyuni; Lollie Agustina Pancawaraswati Putri; Muammar Bakar Murni (Jurnal Manajemen Hutan Tropika, 2015)
Mangrove forest in the context of climate change is important sector to be included in the inventory of greenhouse gas (GHG) emissions. The present study describes land-use and land-cover change during 2006–2012 of a mangrove forest conservation area, Karang Gading and Langkat Timur Laut Wildlife Reserve (KGLTLWR) in North Sumatra, Indonesia and their implications to carbon dioxide emissions. A land-use change matrix showed that the decrease of mangrove forest due to increases of other land-use such as aquaculture (50.00%) and oil palm plantation (28.83%). Furthermore, the net cumulative of carbon emissions in KGLTLWR for 2006 was 3804.70 t CO2-eq year-1, whereas predicting future emissions in 2030 was 11,318.74 t CO2-eq year-1 or an increase of 33.61% for 12 years. Source of historical emissions mainly from changes of secondary mangrove forests into aquaculture and oil palm plantation were 3223.9 t CO2-eq year-1 (84.73%) and 959.00 t CO2-eq year-1 (25.21%), respectively, indicating that the KGLTLWR is still a GHG emitter. Mitigation scenario with no conversion in secondary mangrove forest reduced 16.21% and 25.8% carbon emissions in 2024 and 2030, respectively. This study suggested that aquaculture and oil palm plantation are drivers of deforestation as well as the largest of GHG emission source in this area.